2013
DOI: 10.1144/sp378.19
|View full text |Cite
|
Sign up to set email alerts
|

Timing of geothermal activity in an active island-arc volcanic setting: First 40 Ar/ 39 Ar dating from Bouillante geothermal field (Guadeloupe, French West Indies)

Abstract: Mineral separates of adularia have been extracted from three samples of highly silicified hydrothermal breccias, newly discovered in the active Bouillante geothermal field (Guadeloupe archipelago), and investigated by 40 Ar/ 39 Ar geochronology in order to constrain the timing of geothermal activity in this part of the active Lesser Antilles island arc. The inverse isochron diagram indicates an age of 248 + 50 ka (2s) for all adularia from one breccia sample (n ¼ 8), with an initial 40 Ar/ 36 Ar ratio of atmos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The duration of hydrothermal activity (i.e. timescales for efficient fluids and heat transfers) in high-enthalpy geothermal systems is still a poorly constrained factor, mainly because geochronological studies on active geothermal fields are rare [see review in Verati et al, 2014]. Our results offer an interesting opportunity to address this question.…”
Section: Age and Time-scale Of The Paleo-geothermal System Activitymentioning
confidence: 91%
See 2 more Smart Citations
“…The duration of hydrothermal activity (i.e. timescales for efficient fluids and heat transfers) in high-enthalpy geothermal systems is still a poorly constrained factor, mainly because geochronological studies on active geothermal fields are rare [see review in Verati et al, 2014]. Our results offer an interesting opportunity to address this question.…”
Section: Age and Time-scale Of The Paleo-geothermal System Activitymentioning
confidence: 91%
“…2). The intersection of these two fault families is responsible for the collapse of the central part of the Terre-de-Haut island contemporaneous with the development of a geothermal system similar, if we consider its structural and epithermal settings, to the present-day active Bouillante geothermal system [Bouchot et al, 2010;Calcagno et al, 2012;Patrier et al, 2013;Verati et al, 2014]. Therefore, the exhumed Terrede-Haut geothermal paleo-system offers a unique opportunity to observe an analogue of the deep parts of active high-temperature geothermal systems.…”
Section: Structural Analysis and Finite Deformation Pattern Of Les Samentioning
confidence: 99%
See 1 more Smart Citation
“…This rheological interface is then potentially a preferential pathway for regional heat and fluid transfers, and in connection to the already known fault network and/or to volcanic structures (interfaces between lava flows, volcanic fabrics,...), offering a system of connected physical vertical and more horizontal discontinuities able to drive the hydrothermal fluids circulation at the whole scale of Basse-Terre arc crust. This result opens new exciting perspectives first for the exploration of geothermal resources, only known and already exploited in the Bouillante bay (Bouchot et al, 2010;Calcagno et al, 2012;Verati et al, 2014), and second in a more general way for the understanding of genesis of metallic ore deposits in volcanic arcs, following the idea that epithermal systems are comparable to geothermal systems (White & Hedenquist, 1995).…”
Section: Petrological Evolution Of the Basal Complexmentioning
confidence: 96%
“…Several authors have focused their petrographic and geochemical studies on fresh volcanic rocks of the southern active volcanic part of the archipelago, and most of the studies have concentrated further south or near La Soufrière volcano or Bouillante geothermal field providing a revision of the ages of the volcanic formations and the lithological contours Dagain, 1981;Blanc, 1983;Boudon et al, 1989;Samper et al, 2007Samper et al, , 2009Patrier et al, 2013;Verati et al, 2014;Ricci et al, 2017). A recent study has shown the evolution of petrophysical properties from fresh to hydrothermalized volcanic rocks in the volcanic island of Guadeloupe archipelago (Navelot et al, 2018).…”
Section: Guadeloupe In the Lesser Antilles Geological Contextmentioning
confidence: 99%